The Innovation Of Inclusivity In Public Relations Through The Implementation Of Deaf Interpreter - Nafiah, Hida (Universitas Islam Negeri Raden Intan Lampung, 2024)
The Indonesian government signed the rights of persons with disabilities outlined in the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) on March 30, 2007, in New York. The government's obligation is to realize these rights and ensure that people with disabilities can participate in all aspects of life, including the utilization of technology, information, and communication. This research aims to prove the hypothesis that the implementation of a deaf interpreter can be an innovation of inclusivity in public relations in Indonesian higher education. The researcher analyzed the qualitative content of graduation ceremonies from the best universities across Indonesia that were broadcast on YouTube from 2022 to 2023. Graduation ceremonies were chosen as the research object because they involve many public relations practices during the event. To explore the hypothesis, semiotics was used as a research tradition, complemented by the theory of innovation diffusion. This research confirms that a deaf interpreter can be an innovation of inclusivity in public relations in higher education. This is because it was found that among the many top universities in Indonesia, only a few universities have implemented a deaf interpreter in graduation ceremonies. These include Gadjah Mada University, Brawijaya University, Bandung Institute of Technology, and Padjadjaran University. Other higher education institutions can implement the innovation of a deaf interpreter in graduation ceremonies to create a more inclusive social, educational, cultural, and communicative environment.